Self-assembly to function: design, synthesis and broad spectrum antimicrobial properties of short hybrid E-vinylogous lipopeptides - Shankar, S. Shiva; Benke, Sushil N.; Nagendra, Narem; Srivastava, Prabhakar Lal; Thulasiram, Hirekodathakallu V.; Gopi, Hosahudya N. (Journal of Medicinal Chemistry, 2013)
Nonribosomal E-vinylogous gamma-amino acids are widely present in many peptide natural products and have been exploited as inhibitors for serine and cysteine proteases. Here, we are reporting the broad spectrum antimicrobial properties and self-assembled nanostructures of various hybrid lipopeptides composed of 1:1 alternating alpha-and E-vinylogous residues. Analysis of the results revealed that self-assembled nanostructures also play a significant role in the antimicrobial and hemolytic activities. In contrast to the alpha-peptide counterparts, vinylogous hybrid peptides displayed excellent antimicrobial properties against various bacterial and fungal strains. Peptides that adopted nanofiber structures displayed less hemolytic activity, while peptides that adopted nanoneedle structures displayed the highest hemolytic activity.

Potent antimicrobial activity of lipidated short alpha,gamma-hybrid peptides - Benke, Sushil N.; Thulasiram, Hirekodathakallu V.; Gopi, Hosahudya N. (ChemMedChem, 2017)
Herein we report the potent antimicrobial activity of alpha,gamma-hybrid lipopeptides composed of 1:1 alternating - and gamma-amino acids. Along with their potent antimicrobial activity against various Gram-positive and Gram-negative bacteria, these hybrid lipopeptides were found to be less hemolytic. Studies into the mechanism of action revealed that these short cationic lipopeptides bind and disrupt the bacterial cell membrane. Time-kill kinetics analyses revealed that the potent alpha,gamma-hybrid lipopeptides completely inhibit bacterial growth in less than 20 minutes. Overall, the promising antimicrobial activity along with lower hemolytic activity displayed by these alpha,gamma-hybrid lipopeptides make them well suited for further exploration into the design of potent lipopeptide antibiotics.